(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine the reliability of BI-RADS Classification by evaluating the correlation between BI-RADS Classification System and pathology results of patients admitted to the general surgery outpatient clinic of our hospital with the complaints of breast lump, breast pain and nipple discharge.Material and Methods: This retrospective study was conducted between 2009 and 2011. The study included a total of 150 female patients, who applied to the Research and Training Hospital General Surgery Polyclinics with the complaints of breast lump, pain and discharge which were classified as BIRADS-3, BIRADS-4 (4a, 4b, 4c) subcategories and BIRADS-5 category, and were evaluated using the epicrisis forms, test results (radiological imaging and tumor markers) and pathology reports.Results: The study included a total of 150 patients; 21 of which were classified as BI-RADS 3, 44 as BI-RADS 4a, 35 as BI-RADS 4b, 22 as BI-RADS 4c and 28 as BI-RADS 5. Of the masses determined to be benign, 21 cases (100%) were classified as BI-RADS 3, 43 cases (97.72%) as BI-RADS 4a, 34 cases (97.14%) as BI-RADS 4b, 8 cases (36.36%) as BI-RADS 4 and 1 case as BI-RADS 5 (3.57%). Of the malignant masses, 1 case (2.28%) was classified as BI-RADS 4a, 1 (2.86%) as BI-RADS 4b, 14 cases (63.64%) as BI-RADS 4c and 27 cases (96.43%) as BI-RADS 5.Conclusion: In the light of these data, we believe that the division of BI-RADS category 4 into sub-categories play an important role in management of breast masses.